ENZYME KINETICS OF POLYPHENOL OXIDASE FROM GROS MICHEL BANANA - GARCÍA W., Claudia L.; GIRALDO G., Germán A.; HURTADO T., Hernando; MENDIVIL, Carlos O. (Vitae, 2009)
The post harvest of banana is accompanied by multiple enzymatic reactions, which cause the degradation of starches and chlorophyll, the synthesis of sugars and carotenes, changes in the acidity, tissue softening and enzymatic browning. This browning is caused by the action of the Polyphenoloxidase (PPO) on the phenols contained in the fruit and is considered an undesirable change by the consumer. To determine the time of minimum enzymatic activity in order to obtain its optimal processing, the variety Gros Michelwas characterized in colour, texture, activity of water, humidity and Brix degrees; then its enzyme kinetics were studied by measuring the formation of brown colour with an UV-visible spectrophotometer at 420nm. The amount of total protein (enzyme) was also quantified by the Bradford method (reading at 595 nm). Once the kinetics of each maturation stage were identified, a comparison was made among each of the groups by means of Repeated Measures Analysis of Variance, showing a marked and statistically significant difference among banana of young and old maturation stages in a decreasing manner, finding the minimum point of activity of the enzyme in the most advanced maturation stages.